55 THE PRODUCTION PERFORMANCE OF FODDER SORGHUM ACCORDING TO IRRIGATION SHEETS AND LAND COVER - Sousa, Paulo Gleisson Rodrigues de; Viana, Thales Vinícius de Araújo; Carvalho, Clayton Moura de; Campos, Kilmer Coelho; Silva, Francisco Limeira da; Azevedo, Benito Moreira de (IRRIGA, 2021)
The objective of the present work was to evaluate the productivity and efficiency of the use of the water in the culture of sorghum forager (BRS Black Tip) under different blades of irrigation (50; 75; 100; 125 and 150% of the evapotranspiration of the culture, ETc) associates the different levels of covering deceased (mulch) (0.00; 2.50; 3.75; 5.00 and 6.25 cm). The experimental delineation was made use in subdivided parcels, 5 x 5 with 5 repetitions, having totalized 125 experimental units. It was analyzed: productivity of cool mass, productivity of dry substance, productivity of seed, weight of 100 seed, weight of the seed for panicle, efficiency of use of the water in the production of cool mass in (kg m-3 and R m-3). For the results it was possible to conclude that, the factors of production in irrigation blades and in bagana coverage had been promising for the productivity of the culture of sorgo; The significant effect for efficiency in the use of the water in the 0 variable of productivity of cool biomass and dry substance in kg m-3 and R m-3, indicate this being a promising culture for the region, associated with the adopted techniques of culture in the present work.